Hacks: Season One Season one - Aniello, Lucia; Downs, Paul W.; Statsky, Jen, 1985-; Calo, Joanna; Law, Andrew; Akhavan, Desiree, 1984-; Smart, Jean; Einbinder, Hannah; Abdoo, Rose, 1962-; Studio Distribution Services (Firm) (Universal City, CA : SDS, 2022)
Tells the story of an unlikely bond that forms between a veteran comedian and her ambitious young writer.
There is no line -- Primm -- A gig's a gig -- D'jewelry -- Falling -- New eyes -- Tunnel of love -- 1.69 million -- Interview -- I think she will.
Originally broadcast on television in 2021 ; 2022 DVD release.
new dvd 2024 fall.
Jean Smart, Hannah Einbinder, Rose Abdoo, Carl Clemons-Hopkins, Christopher McDonald.
Not rated.
DVD ; Dolby digital 5.1 ; anamorphic widescreen ; NTSC Region 1.
English dialogue ; subtitled for the deaf and hard of hearing (SDH).
Keywords: Women comedians -- Nevada -- Las Vegas -- Drama; Women authors -- Drama -- Nevada -- Las Vegas; Mentoring -- Drama; Road television programs; Television series; Fiction television programs; Video recordings for the hearing impaired; Comedy television programs